A Lump-Integral Model Based Freezing and Melting of A bath Material Onto a Cylindrical Additive of Negligible Resistance - Singh, Umesh Chandra; Prasad, Anant; Kumar, Arbind (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
In a theoretical analysis, a lump-integral model for freezing and melting of the bath material onto a cylindrical additive having its thermal resistance negligible with respect to that of the bath is developed. It is regulated by independent non-dimensional parameters, namely the Stefan number, St the heat capacity ratio, Cr and the modified conduction factor, Cofm. Series solutions associated with short times for time variant growth of the frozen layer and rise in interface temperature between the additive and the frozen  layer are obtained. For all times, numerical solutions concerning the frozen layer growth with its melting and increase in the interface temperature are also found. Time for freezing and melting is estimated for different values of Cr, St and Cofm. It is predicted that for lower total time of freezing and melting Cofm